An effective approach for purifying, cutting, and functionalising of multi-walled carbon nanotubes. (1st December 2013) - He, F.-A.; Fan, J.-T.
<x xml:space="preserve">Abstract</x> High purity, homogenous dispersion, and good compatibility of carbon nanotubes (CNTs) in polymer composites are key factors to achieve excellent mechanical and electrical properties of polymer/CNTs composites. Although extensive efforts have been made in this area, it is still crucial to explore an effective method to purify, cut, and functionalise CNTs. Here the authors report an approach to purify, cut, and functionalise multi-walled carbon nanotubes (MWCNTs) simultaneously using KMnO4 as an oxidant in the presence of a phase transfer catalyst (PTC). The purification, cutting, and functionalisation of CNTs were confirmed by the results of energy dispersive spectroscopy (EDS), transmission electron microscope (TEM), hydrodynamic radius characterisation, Raman, X-ray photoelectron spectroscopy (XPS) analyses, and ultraviolet-visible (UV-vis) spectroscopy. It was found that the modified CNTs are easily dispersible in a range of commonly used organic solvents, which provides an effective way to prepare polymer/CNT composites by solution blending.